2023
DOI: 10.1523/jneurosci.0428-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Layer 5 Intratelencephalic Neurons in the Motor Cortex Stably Encode Skilled Movement

Takanori Shinotsuka,
Yasuhiro R. Tanaka,
Shin-Ichiro Terada
et al.

Abstract: The primary motor cortex (M1) and the dorsal striatum play a critical role in motor learning and the retention of learned behaviors. Motor representations of corticostriatal ensembles emerge during motor learning. In the coordinated reorganization of M1 and the dorsal striatum for motor learning, layer 5a (L5a), which connects M1 to the ipsi- and contra-lateral dorsal striatum, should be a key layer. Although M1 L5a neurons represent movement-related activity in the late stage of learning, it is unclear whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Motor cortex provides the main excitatory input to dorsal striatal SPNs and has been shown to be important for both motor learning and execution of movement (Currie et al , 2022; Park et al , 2022, Shinotsuka et al , 2023). We therefore tested whether the preserved mature spines and arbors on dSPNs observed in VGLUT3 KO (and eDREADD+CNO) mice after dopamine depletion reflect the preservation of cortical inputs to dSPNs (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Motor cortex provides the main excitatory input to dorsal striatal SPNs and has been shown to be important for both motor learning and execution of movement (Currie et al , 2022; Park et al , 2022, Shinotsuka et al , 2023). We therefore tested whether the preserved mature spines and arbors on dSPNs observed in VGLUT3 KO (and eDREADD+CNO) mice after dopamine depletion reflect the preservation of cortical inputs to dSPNs (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Since the circuit already has PT neurons, which can seemingly do a similar computation more accurately, what could ITs be doing? ITs have been implicated in learning, forming internal models, and preparatory behavior (Salaj et al, 2021), and a recent study showed that learned-but not unlearned-motor behaviors were robustly represented in IT cells of M1 (Shinotsuka et al, 2023). It is possible that ITs’ sharp encoding of preferred object location is partially learned and changes through exposure to behaviorally relevant tasks and stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…These neurons also project to CSNs 39 . Contralateral cortex-and striatum-projecting neurons are associated with motor command-like activities, and inactivation of layer Va affects lever task movements [49][50][51] .…”
Section: Discussionmentioning
confidence: 99%